The ethnobotany and ethnopharmacology of Gentianella alborosea (Gilg) Fabris and Gentianella nitida (Griseb.) Fabris (family Gentianaceae) used in Peru: A review - Rubio-Guevara, Susana; Olascuaga-Castillo, Karyn; Blanco-Olano, Cyntia; Valdiviezo-Campos, Juan (Ethnobotany Research and Applications, 2020)
Background: The species Gentianella alborosea (Gilg) Fabris and Gentianella nitida (Grisebach) Fabris (Gentanaceae family) are widely used in traditional medicine in Peru, under the name of "hercampuri", mainly to relieve stomach pain, such as hepatoprotective, purifying, hypoglycemic, diuretic and for the treatment of obesity and hypercholesterolemia. Review objective: The objective of this review is to describe the ethnobotanical and ethnopharmacological characteristics of G. alborosea and G. nitida, in order to increase the development of the scientific database that justifies and optimizes the uses of Peruvian medicinal plants. Materials and Methods: A search was carried out in databases and academic search engines Google, Scielo, Scopus and PubMed with the terms' Gentianella alborosea ', Gentiana alborosea Gilg,' Gentianella nítida ',' Gentianella ',' Gentianáceas', ' hercampuri 'using boolean operators. Results: Both species are used interchangeably under the name "hercampuri" and their main indication is for the treatment of liver diseases, hypercholesterolemia and diabetes. Its phytochemistry shows the presence of alkaloids, xanthones, flavonoids and phenolic compounds, differentiated by the types of secoiridoids and / or sesterterpenes, responsible for its biological activity. Conclusions: G. alborosea has not shown hepatoprotective, hypoglycemic and lipid-lowering effects since none of the in vitro and in vivo studies show conclusive results, however it is safe in the doses used in traditional medicine. In contrast, G. nitida did demonstrate hypoglycemic, lipid-lowering, antifungal, antibacterial, in vitro antioxidant, and hepatoprotective effects. According to the above, it would be more advisable to use G. nitida under the name "hercampuri" in traditional medicine. Key words: hercampuri, hepatoprotective, phytochemistry, biological activity, xanthones, amarogentine